Plant uses in different Bronze and Iron Age settlements from the Nuoro province (Sardinia). The results of phytolith analyses from several ceramic fragments and grinding stones - ALBERT, Rosa M.; PORTILLO, Marta (Complutum, 2005)
Sin resumen